Review of Solier's Mecorhopalus species (Coleoptera: Staphylinidae: Aleocharinae) - Moussallem, M.; Ribeiro-Costa, C. S.; Caron, E. (Zootaxa, 2014)
Antoine Joseph Jean Solier, a French naturalist, described 53 species of Staphylinidae of the Chilean fauna, among them three species in a new genus Mecorhopalus (M. ater, M. bipustulatus and M. elongatus). Today these species are regarded as Aleochara atra, A. solieri and A. mutare , respectively. The objective of this study is to provide an updated description and nomenclatural status of these species. Mecorhopalus remains as junior synonym of Aleochara with one species in the subgenus Aleochara and another in Coprochara. Through study of the type material, A. mutare is synonymized with A. solieri as junior subjective synonym.